Immunophenotyping for haematologists : principles and practice - Bain, Barbara J; Leach, Richard M (Wiley-Blackwell, 2021)
"The increasing centralisation of specialised tests and the divorce of clinical and laboratory haematology in many countries means that many haematologists now have no direct contact with an immunophenotyping laboratory. Despite this, the results from the laboratory are often crucial in the management of their patients. This book is intended to help haematologists and trainees to understand and interpret immunophenotyping results. It is not directed at those working in an immunophenotyping laboratory and technical details are therefore outlined only briefly. Such laboratories may, however, find it a useful source of information. For further reading on the subject, see the bibliography of each chapter"--
Keywords: Hematologic Tests; hematologické testy; Immunophenotyping; imunofenotypizace; hematologie a transfuzní lékařství